Constructing Spirituality in the Cognitive Science of Religion - Stoddard, Brad (Method & theory in the study of religion, 2020)
Seven researchers in the growing field of the cognitive science of religion recently claimed to have documented the unique neural correlates of spirituality separate from and independent of religion. They claimed that spirituality is therefore a natural part of human cognition and suggested that they proved definitively that spirituality is substantively different than religion. Using insights developed by scholars associated with the critical religion approach to the academic study of religion, this article identifies a series of methodological errors that undermine the researchers’ project and that potentially impacts the larger academic study of the cognitive science of religion.